Control Concepts and Creative Thinking Skills Basic School Students Through RME Learning Approaches - Kurniasih, Asih; Rahman, Rahman; Agustin, Mubiar; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2020)
The purpose of this study was to examine is there increasing mastery of concepts and creative thinking skills of students after learning approaches given Realistic Mathematics Education (RME). The study involved students in grade 3 in SDN 2 Jamblang by the number of 35 students composed of male students and 18 female students 17 people. The method used is classroom action research (PTK), which consists of two cycles with each cycle through the stages of preparation, action, action observation, and reflection. Data were obtained through observation and tests. From the initial data known number of students who completed 18 students and 17 students who have not completed. After action by RME results showed an increase, the data of 28 students completed and unresolved 7 student